Causal processes of shallow and deep seismicity at Campi Flegrei caldera - Genny Giacomuzzi; Rossella Fonzetti; Aladino Govoni; Pasquale De Gori; Claudio Chiarabba (Communications Earth & Environment)
Abstract The increase of ground deformation, seismicity, and gas emission is underlining a remarkable unrest at Campi Flegrei caldera. The direct involvement of magma has been invoked to explain the deformation and space/time changes of velocity anomalies at shallow crustal depths. Here, we show that detailed imaging of seismicity, improved by phase detection with machine-learning algorithms, and velocity models shed light on the active processes at the unresting caldera. Shallow seismicity tracks the fluids uprise, while deeper seismicity, aligning on an almost continuous ring on the top of the inferred magmatic source, indicates deep-seated-related, induced stresses. Our results offer valuable constraints to the challenging aspects of tracking upward migration of magma and magmatic fluids from depth, crucial in terms of hazard assessment and forecasting at Campi Flegrei.